PENINGKATAN KUALITAS PRODUK UKM KURSI LIPAT DENGAN METODE INTERNAL PRESSURE DAN RANCANG BANGUN MESIN BENDING KONVENSIONAL - Yuni Hermawan; Santoso Mulyadi (ROTOR, 2013)
Product with quality obtained from existence of good forming process. Ovality one of deviation which is because of process bending. Process bending donewithout and internal  pressure. Internal pressure used: 100, 200, 250 and 300 bar. Equipments used in course of bending consisted of the hydraulic pump, pressure gauge, regulator / valve, T Fitting, Oli SAE 40 and Nivle Pipe ( NPT).For that require to be a research to analyse the hydraulic pressure influence to ovality process of bending of pipe of circular of raw material camp chair. Research done to designed experiment with the diameter tube 16, 19.05 and 25.4 mm. Its result hydraulic pressure yielding ovality minimum is for the D of tube 16 mm equal to 300 bar while for the D of tube 19.05 and 25.4 equal to 250 bar. Keywords: bending process, ovality and hydraulic pressure.